Quality of life and participation in daily life of adults with Pompe disease receiving enzyme replacement therapy: 10 years of international follow‐up. Issue 2 (3rd November 2015) - Güngör, Deniz; Kruijshaar, Michelle E.; Plug, Iris; Rizopoulos, Dimitris; Kanters, Tim A.; Wens, Stephan C. A.; Reuser, Arnold J. J.; van Doorn, Pieter A.; van der Ploeg, Ans T.
Summary: Background: Pompe disease is an inheritable metabolic disorder for which enzyme replacement therapy (ERT) has been available since 2006. Effects of ERT have been shown on distance walked, pulmonary function and survival. We investigated whether it also improves quality of life and participation in daily life in adult patients with the disease. Methods: In an international survey, we assessed quality of life (Short Form 36, SF‐36) and participation (Rotterdam Handicap Scale, RHS) annually between 2002 and 2012. Repeated measurements mixed effects models were used to describe the data over time. Results: Responses were available for 174 adult patients. In the periods before and after start of ERT, the median follow‐up times were 4 years each (range 0.5‐8). The SF‐36 Physical Component Summary measure (PCS) deteriorated before ERT (‐0.73 score points per year (sp/y); CI 95 % ‐1.07 to ‐0.39), while it improved in the first 2 years of ERT (1.49 sp/y; CI 0.76 to 2.21), and remained stable thereafter. The Mental Component Summary measure (MCS) remained stable before and during ERT. After declining beforehand (‐0.49 sp/year; CI ‐0.64 to‐0.34), the RHS stabilized under ERT. Conclusion: In adult patients with Pompe disease, ERT positively affects quality of life and participation in daily life. Our results reinforce previous findings regarding the effect of ERT on muscle strength, pulmonary function and survival.